Status of conservation evaluation of springs in watersheds - Pieroni, Juan Pedro [UNESP]; Rodrigues Branco, Karina Grisólia; do Valle Dias, Graco Ribeiro [UNESP]; Ferreira, Gilda Carneiro [UNESP] (My University, 2019)
The study of springs in hydrographic basin is an important instrument to the management of the conservation and preservation of water resource aiming water production. In face of this challenge, this article evaluates the state of conservation of springs from the watershed of Córrego Ibitinga, located in Rio Claro (SP). The methodology adopted analyzed the state of conservation based in the evaluation of macroscopic parameters. The parameters used allowed to evaluate, in an integrated mode, the physics, biologics and socioeconomic impacts on springs. Using the Index of Environment Impact at springs, the parameters measured and the statistic treatment of the data enabled the classification of the springs into five levels of conservation: great, good, reasonable, bad and poor. The results revealed the most expressive parameters for the degradation process at the springs studied and frequency of occurrence of impacts in relation to the levels of conservation. The springs indicated several aspects of degradation, due to direct or indirect anthropogenic action. From the 39 springs studied, 75% were concentrated in the three worst levels. The results enabled the conclusion which the springs showed high level of degradation, and that the state of conservation of springs is inherent to the proximity with roads and the absence of local protection and of vegetation, being those the most frequent impacts.
Avaliação do estado de conservação de nascentes em microbacias hidrográficas
Keywords: Index of environment impact at springs; Water production; Water resources